Association of cardiovascular risk factors and myocardial hypertrophy in women with preeclampsia history - Ferreira, Ricardo Mattos [UNESP]; Ferron, Fabiane Valentini Francisqueti [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Peraçoli, José Carlos [UNESP]; Ferron, Artur Junio Togneri [UNESP]; Roscani, Meliza Goi; Hueb, João Carlos [UNESP]; Bazan, Rodrigo [UNESP]; Martin, Luis Cuadrado [UNESP]; Bazan, Silméia Garcia Zanati [UNESP] (Elsevier, 2024)
Aims: A historic of preeclampsia (PE) has been associated with cardiovascular disease (CVD) in women. There are substantial evidences that cardiovascular changes resulting from PE can persist even after pregnancy end. Therefore, the aims was to evaluate the prevalence of myocardial hypertrophy in young women 12 months after PE event as well as try to identify risk factors for these changes. Materials and methods: Single-center observational prospective cross-sectional study that included 118 consecutive patients after 12 months of PE. Clinical and laboratory evaluations, echocardiogram were performed. Myocardial hypertrophy (LVH) was defined as an index myocardial mass ≥ 45 g/m2.7, for women. Classical risk factors for CVD were considered. Analysis included linear or logistic regression and Spearman's correlation coefficient. Significance level of 5 %. Key findings: Systemic arterial hypertension (SAH) was identified in 52 patients (44 %), overweight/obesity (OOB) in 82 (69 %), dyslipidemia in 68 (57 %) and metabolic syndrome in 47 patients (40 %). LVH was present in 35 cases (29 %) and associated with OOB (OR = 4.51; CI95%:1.18–17.17, p < 0.001), in a model corrected for age and SAH diagnosis. When only the metabolic syndrome components were analyzed, in the multiple logistic regression model, the abdominal circumference was the only clinical variable associated with LVH (OR = 17.65; CI95%:3.70–84.17; p < 0.001). Significance: It was observed a high prevalence of ventricular hypertrophy in young women with a history of pre-eclampsia. This condition was associated with the presence of obesity.
Keywords: Cardiovascular risk; Echocardiography; Myocardial hypertrophy; Preeclampsia